Parasitoids associated with the invasive pest Drosophila suzukii (Diptera: Drosophilidae) in Argentina and their potential role as biological control agents of this pest in blueberry orchards - Funes, Claudia Fernanda; Gallardo, Fabiana Edith; Reche, Vanina Anadina; Escobar, Lorena Ines; Ovruski Alderete, Sergio Marcelo; Kirschbaum, Daniel Santiago (International Society for Horticultural Science (ISHS), 2023)
Trabajo presentado al XII International Vaccinium Symposium